2012
DOI: 10.1001/archinternmed.2012.3203
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and Long-term Cognitive Trajectory Among Persons With Dementia

Abstract: Background Delirium is characterized by acute cognitive impairment. We examined the effect of delirium on long-term cognitive trajectory in older adults with Alzheimer's disease (AD). Methods Prospectively collected longitudinal data from a nested cohort of hospitalized patients with AD (n=263) in the Massachusetts Alzheimer's Disease Research Center Patient Registry during 1991–2006 (median follow-up: 3.2 years). Cognitive function was measured using the Information-Memory-Concentration (IMC) section of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(153 citation statements)
references
References 65 publications
(72 reference statements)
5
134
0
5
Order By: Relevance
“…Delirium, in general, is associated with a worsening of dementia [1], increased hospital costs [2], and increased mortality [3]. Postoperative delirium (POD), occurring in the days to weeks after surgery, has also been linked to cognitive decline and increases in mortality, particularly in elderly patients [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Delirium, in general, is associated with a worsening of dementia [1], increased hospital costs [2], and increased mortality [3]. Postoperative delirium (POD), occurring in the days to weeks after surgery, has also been linked to cognitive decline and increases in mortality, particularly in elderly patients [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In the SAGES (Successful Aging after Elective Surgery) study, Inouye et al reported biphasic behaviour in patients with and without cognitive decline: major cognitive decline occurred after one month, a comparable recovery of function was observed after two months, but, most importantly, an accelerated decline was observed, in patients, 36 months after anaesthesia or surgery [9]. Gross et al confirm that POCD, following delirium, can accelerate the cognitive decline in Alzheimer's patients [10].…”
Section: Deliriummentioning
confidence: 97%
“…For example, a person who was able to function at home but then requires hospitalization because of an injury may experience a persistent reduction in cognitive ability that continues beyond the initial hospitalization. 9 The reduction of preventable hospitalizations or emergency department visits is therefore often cited as an important quality goal for the patient and the health system overall. These quality guidelines remain largely aspirational, however, because of the immense challenges involved in meeting them.…”
Section: Progress In the Statesmentioning
confidence: 99%